GET COO TRAVEL: quando l’intelligenza artificiale incontra l’arte - Grasso, Roberta (Archeomatica, 2018)
GetCOO Travel is an innovative travel app for Android and iOS that, using image recognition, identifies monuments and artworks. GETCOO, that developed this app, is a very promising startup that works in the Computer Vision field. GETCOO developed a proprietary Artificial Intelligence technology named DART (Direct Acquisition and ReTrieval) that can identify not just generic categories but also specific objects. DART can be applied to identify basically anything, including monuments and artworks. GetCOO Travel works worldwide indoor and outdoor. With a single travel app, tourist can discover information about monuments and artworks simply by shooting them a photo. A smarter, lighter and more scalable solution with respect to dedicated apps, QR-codes and beacons.